Histone H3K27 demethylase KDM6A is an epigenetic gatekeeper of mTORC1 signalling in cancer. Issue 8 (11th September 2021) - Revia, Steffie; Seretny, Agnieszka; Wendler, Lena; Banito, Ana; Eckert, Christoph; Breuer, Kersten; Mayakonda, Anand; Lutsik, Pavlo; Evert, Matthias; Ribback, Silvia; Gallage, Suchira; Chikh Bakri, Ismaiel; et al.
Abstract : Objective: Large-scale genome sequencing efforts of human tumours identified epigenetic modifiers as one of the most frequently mutated gene class in human cancer. However, how these mutations drive tumour development and tumour progression are largely unknown. Here, we investigated the function of the histone demethylase KDM6A in gastrointestinal cancers, such as liver cancer and pancreatic cancer. Design: Genetic alterations as well as expression analyses of KDM6A were performed in patients with liver cancer. Genetic mouse models of liver and pancreatic cancer coupled with Kdm6a-deficiency were investigated, transcriptomic and epigenetic profiling was performed, and in vivo and in vitro drug treatments were conducted. Results: KDM6A expression was lost in 30% of patients with liver cancer. Kdm6a deletion significantly accelerated tumour development in murine liver and pancreatic cancer models. Kdm6a-deficient tumours showed hyperactivation of mTORC1 signalling, whereas endogenous Kdm6a re-expression by inducible RNA-interference in established Kdm6a-deficient tumours diminished mTORC1 activity resulting in attenuated tumour progression. Genome-wide transcriptional and epigenetic profiling revealed direct binding of Kdm6a to crucial negative regulators of mTORC1, such as Deptor, and subsequent transcriptional activation by epigenetic remodelling. Moreover, in vitro and in vivo genetic epistasis experiments illustrated a crucial function of Deptor and mTORC1 in Kdm6a-dependent tumour suppression. Importantly, KDM6A expression in human tumours correlates with mTORC1 activity and KDM6A-deficient tumours exhibit increased sensitivity to mTORC1 inhibition. Conclusion: KDM6A is an important tumour suppressor in gastrointestinal cancers and acts as an epigenetic toggle for mTORC1 signalling. Patients with KDM6A-deficient tumours could benefit of targeted therapy focusing on mTORC1 inhibition.